(untitled) (REMUNOM, 2024)
The present work aims to analyze the phenomenon of "Pejotization" from the perspective of labor legislation and jurisprudence in the employment relationship, where it is fraud or reward. Materials and Method: thus, the repercussion of this institute on labor law will be analyzed, with judgmental presentation, and briefly some effects within this labor relationship will be punctuated. Results: the study shows a brief analysis of the historical evolution of Labor Law, differentiating the concepts of work and employment, presenting the existing affinity between work relationships and the precariousness of these relationships and, sometimes, some situations of pseudo-benefit. Final considerations: The work relationship of the "Pejotization" is evidenced by greater gains on the part of the employer, being possible, however, for the "pejotized" employee to obtain positive financial results.